2020
DOI: 10.3390/ijms21062036
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Salt Sensitivity and Osmotic Fragility in the Development of Cerebral Small Vessel Disease

Abstract: Increased salt intake in food probably affects the progression of cerebral small vessel disease (CSVD), which justifies the study of disturbances in sodium homeostasis associated with the development of CSVD. We aimed to clarify the role of salt sensitivity and osmotic fragility in the development of CSVD. Erythrocyte salt sensitivity was measured using the modified salt blood test, and osmotic fragility was measured using the classic osmotic fragility test in 73 patients with CSVD (48 women; 60.1 ± 6.5 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“… 9 ESS is a marker of erythrocyte sodium sensitivity and other studies have shown a relation between ESS and self‐reported sodium consumption, cerebrovascular disease, and end‐stage kidney disease. 30 , 31 , 32 Thus, ESS might be related to vascular damage, though our study does not support it as a good measure of SS of BP.…”
Section: Discussioncontrasting
confidence: 74%
“… 9 ESS is a marker of erythrocyte sodium sensitivity and other studies have shown a relation between ESS and self‐reported sodium consumption, cerebrovascular disease, and end‐stage kidney disease. 30 , 31 , 32 Thus, ESS might be related to vascular damage, though our study does not support it as a good measure of SS of BP.…”
Section: Discussioncontrasting
confidence: 74%
“…6–8. 1758 An additional 14 studies were excluded from the meta-analyses as they were repeated publications from the same cohort (n = 8); without complete data for meta-analysis (n = 4); and with unclear results reporting (n = 2). For multiple publications from the same cohort, we selected a representative study from each cohort based on the following: a greater number of cSVD markers reported, preference for more recent publications, and larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of significant differences in ABPM results related to BBB permeability between patients and controls allow us to hypothesize the presence of additional factors of endothelial damage and increased BBB permeability alongside hypertension. These factors may be chronic inflammation 50 or high salt sensitivity, which have been found to independently correlate with CSVD 51 .…”
Section: Discussionmentioning
confidence: 99%